Vaccine: friend or foe? Double seropositive vasculitis following influenza vaccination. Issue 5 (31st May 2019) - Norton, Benjamin; Kon, Sui Phin; Perera, Ranmith; Hull, Richard
Abstract: Administration of the influenza vaccine has been associated with development of several autoimmune phenomena. We describe the case of a 72-year-old male who developed double seropositive vasculitis following seasonal influenza vaccination. On presentation, he was positive for both myeloperoxidase anti-neutrophil cytoplasmic antibody and anti-glomerular basement membrane antibody. He had stage three acute kidney injury requiring dialysis and was treated with methylprednisolone, intravenous cyclophosphamide and plasma exchange. He was also noted to have an incidental seven centimetre abdominal aortic aneurysm. He achieved remission with recovery in renal function and became haemodialysis independent. We hypothesize that the temporal relationship between influenza vaccination and double seropositive vasculitis directly triggered a systemic immune response in a susceptible patient, although a causal relationship cannot be proved. To the best of our knowledge, this is the first case of double seropositive vasculitis occurring in close temporal association with seasonal influenza vaccination.